Accuracy of power Doppler ultrasonography in the diagnosis and monitoring of idiopathic inflammatory myopathies. (22nd June 2022) - Conticini, Edoardo; Falsetti, Paolo; Grazzini, Silvia; Baldi, Caterina; D'Alessandro, Roberto; Al Khayyat, Suhel Gabriele; Biasi, Giovanni; Bellisai, Francesca; Bardelli, Marco; Gentileschi, Stefano; Garcia-Gonzalez, Estrella; Volpi, Nila; et al.
Abstract: Objectives: No clear-cut guidelines exist for the use of imaging procedures for the diagnosis of idiopathic inflammatory myopathies (IIM). The aim of the present study was to assess the diagnostic accuracy of power Doppler ultrasonography (PDUS) score in IIM patients compared with a control group and its usefulness during follow-up. Methods: All patients evaluated in the Vasculitis and Myositis Clinic, Rheumatology Unit, University of Siena were prospectively collected. All patients underwent US examination of both thighs in axial and longitudinal scans, which were also performed twice (T1) or three times (T2). Results: Forty-five patients with IIM (median [interquartile range] age 55 [45–66] years; 35 female) were enrolled. Receiver operating characteristic curves distinguished patients and controls based on ∑power Doppler (PD), ∑oedema, ∑atrophy and CRP. The best cut-off value for ∑PD was 0.5, ∑oedema 1.5, ∑atrophy 0.5 and CRP 0.22 mg/dl. In a logistic regression analysis, the variables that most influenced diagnosis of IIM were ∑PD and ∑oedema ( P = 0.017 and P = 0.013, respectively). ∑Oedema was lower at T1 ( P = 0.0108) and T2 ( P = 0.0012) than at T0. Likewise, ∑PD was lower at T1 ( P = 0.0294) and T2 ( P = 0.0420) than at T0. Physician global assessment was lower at T1 ( P = 0.0349) and T2 ( P = 0.0035) than at baseline. Conclusion: Our findings show that PDUS is a reliable diagnostic tool in the differential diagnosis between inflammatory and non-inflammatory myopathies. Moreover, PDUS can be employed also during the follow-up of patients with IIM. A reduction in disease activity, measured by physician global assessment, led to a concomitant decrease in both oedema and PD, which was directly correlated with their rate of change. This underlines the close link between clinical assessment and PDUS findings, not only at diagnosis but also during monitoring.